KEDUDUKAN KREDITOR ASING PEMEGANG CESSIE DALAM PROSES PKPU DAN KEPAILITAN DI INDOENSIA: PERSPEKTIF KEADILAN DAN NEGARA BERDAULAT: The Position of Foreign Creditors Holding Cessie in PKPU and Bankruptcy Process in Indonesia: Perspective of Justice and Sovereign State - Ngantung, Verra Yanti (Jurnal Globalisasi Hukum., 2025)
The development of bankruptcy and PKPU law in Indonesia demonstrates the complexity in regulating creditors' rights, particularly foreign creditors holding cessie (assignment of claims). Cessie transactions often involve cross-border elements, which complicate debt settlement for debtors undergoing PKPU or bankruptcy proceedings. Several cases, such as PT Visi Media Asia Tbk (VIVA) suing foreign creditors, highlight challenges related to the recognition of foreign creditors' rights in PKPU processes. Furthermore, Indonesian legal provisions, such as restrictions on foreign ownership of land, exacerbate the recognition of foreign creditors in the assignment of receivables. The author defines two key research questions: First, the position of foreign creditors holding cessie in the PKPU and bankruptcy processes in Indonesia, in relation to the principle of state sovereignty in regulating debt payment obligations involving foreign parties; and second, whether the existing regulations in Indonesia's PKPU and bankruptcy processes concerning cessie holders can provide legal certainty and fairness for foreign creditors. This study employs a normative legal research approach, in which the author examines relevant legal concepts and regulations, and analyzes books, journals, and other necessary documents. The research findings and conclusions indicate that within Indonesia’s legal system, bankruptcy and PKPU are mechanisms designed to settle debtors' debts fairly and proportionally, under the supervision of judges and curators. Cessie, as the transfer of claims between creditors, plays an important role in this process, even though it is not explicitly regulated in the Bankruptcy and PKPU Law. While the assignment of receivables can be carried out without the debtor's consent, it still affects the debtor's obligations and the creditors' rights. Moreover, the involvement of foreign creditors in PKPU and bankruptcy processes presents challenges, especially regarding cross-border insolvency and international legal recognition. Therefore, Indonesia needs to clarify legal mechanisms that accommodate the rights of foreign creditors, ensure equal protection for both domestic and foreign creditors, and avoid legal uncertainty through the harmonization of national regulations with international law.